The cultural and political context of the lives of people with dementia in Kerala, India - LOUISE F. MCCABE (Dementia 5(1), 2006, 2006)
This article draws on available literature and empirical data to discuss the experiences of people with dementia in Kerala, India. India is currently undergoing considerable demographic change. The state of Kerala in the south-west of the country is demographically advanced in comparison with other parts of India and as such is experiencing demographic change and modernization ahead of other parts of the country. The proportion and numbers of older people in Kerala are increasing, which in turn is leading to a higher prevalence of dementia. This article reviews existing literature to describe the context for people with dementia in Kerala. It also draws on empirical data to further illustrate and explore their experiences. People with dementia in Kerala are disadvantaged, as the process of modernization is breaking down traditional forms of care ahead of any significant service provision to replace them. Recent development of services in Kerala aims to provide quality care for people with dementia to counteract these demographic changes.